KCa2 and KCa3 Channels in Learning and Memory Processes, and Neurodegeneration - Kuiper, Els F.; Nelemans, Ad; Luiten, Paul G.; Nijholt, Ingrid M.; Dolga, Amalia M.; Eisel, Uli L. (Frontiers in Pharmacology, 2012)
Calcium-activated potassium (KCa) channels are present throughout the central nervous system as well as many peripheral tissues. Activation of KCa channels is essential for maintenance of the neuronal membrane potential and was shown to underlie the afterhyperpolarization (AHP) that regulates action potential firing and limits the firing frequency of repetitive action potentials. Different subtypes of KCa channels were anticipated on the basis of their physiological and pharmacological profiles, and cloning revealed two well defined but phylogenetic distantly related groups of channels. The group subject of this review includes both the small-conductance KCa2 channels (KCa2.1, KCa2.2, and KCa2.3) and the intermediate-conductance (KCa3.1) channel. These channels are activated by submicromolar intracellular Ca2+ concentrations and are voltage independent. Of all KCa channels only the KCa2 channels can be potently but differentially blocked by the bee-venom apamin. In the past few years modulation of KCa channel activation revealed new roles for KCa2 channels in controlling dendritic excitability, synaptic functioning and synaptic plasticity. Furthermore, KCa2 channels appeared to be involved in neurodegeneration, and learning and memory processes. In this review, we focus on the role of KCa2 and KCa3 channels in these latter mechanisms with emphasis on learning and memory, Alzheimer’s disease and on the interplay between neuroinflammation and different neurotransmitters/neuromodulators, their signalling components and KCa channel activation.